Financing Advantage of Green Corporate Asset-Backed Securities and its Impact Factors: Evidence in China - Zhao, Yunfeng; Yue, Yiming; Wei, Ping (Frontiers in Energy Research, 2021)
As an innovative green financial tool, green corporate asset-backed securities can effectively solve the problems of narrow financing channels and maturity mismatches for green projects, which can help achieve green and low-carbon development, carbon peaking, and carbon neutrality goals. In this paper, we examine the financing cost advantages of green corporate asset-backed securities and the related impact factors through a combination of empirical and case studies. Empirical research based on the propensity score matching method (PSM) shows that China’s green corporate asset-backed securities issuance rates are 36.97 bps lower than traditional corporate asset-backed securities on average. Credit rating, issuance scale, issuance interest rate, issuance period, and green factors have become the main impact factors of green corporate asset-backed securities financing advantages.